Perceived time pressure and the Iowa Gambling Task - Michael A. DeDonno; Heath A. Demaree (Judgment and Decision Making, 2008)
The purpose of the present study was to investigate the effect of perceived time pressure on a learning-based task called the Iowa Gambling Task (IGT). One hundred and sixty-three participants were randomly assigned to one of two groups. The experimental group was informed that the time allotted was typically insufficient to learn and successfully complete the task. The control group was informed that the time allotted was typically sufficient to learn and successfully complete the task. Both groups completed the IGT and performance was recorded. The major finding was that participants who were advised that the amount of time allotted was typically insufficient to complete the task performed significantly worse than those who were advised that time was typically sufficient to complete the task.